Penerapan Metode Forecast Exponential Smoothing pada Jumlah Pasien Puskesmas - Dwi Aprilia (Universitas Airlangga, 2016)
Exponential smoothing was forecast method with reducing fl uctuations of forecast results used data from the past. Increasing the number of patients had to was accompanied by facilities and tools supporting adequate services. The research purposed to predict the number of patient the health center Mulyorejo. The results showed that number of patient the health center Mulyorejo fl uctuating every month. Results of forecast in 2016 increasing total patients there in April in the amount 3367 of patients. This also happened on general clinic with a number of patients amount 2643 of pastient. Increasing patient on poli gigi and poli KIA were on October and November amount 322 and 529 patients. MAPE value was produced the forecast total patient was 8,742, general clinic was 6,069, teeth poly was 12,579, and KIA poly was 23,139. Fluctuations in the number of patient visits the health center Mulyorejo more infl uenced by the number of patient visits in general clinic. Suggestions are expected for policy makers should be related planning tools, medicine, and health personnel needed in which the predicted number of visits will be increased in each poli in Puskesmas Mulyorejo.